Penerapan Aplikasi E-Tilang dalam Penyelesaian Perkara Lalu Lintas Jalan - Chaerani Nur, Nurul (Faculty of Law, Institut Ilmu Sosial dan Bisnis Andi Sapada., 2021)
This study aims to determine and analyze the effectiveness of the application of the e-Tilang application in road traffic cases in the jurisdiction of the Biak Numfor Police Resort, Papua. As well as knowing and analyzing the obstacles faced in the implementation of e-Tilang in road traffic violations in the jurisdiction of the Biak Numfor Police Resort, Papua. This research uses juridical-empirical research method. The results showed that the implementation of e-Tilang in Biak Numfor-Papua was not yet effective, because it was not in accordance with the expected goals of the e-Tilang program. It should be done electronically (without using a ticket), but in practice it still uses a ticket. In addition, there are still many people who do not know the procedure for resolving traffic violations with e-tickets, making it difficult to process fines and take confiscated goods beforehand. In addition, there is not yet optimal coordination between authorized agencies that are directly related to the e-Tilang program. The lack of socialization in the community is also an obstacle so that many people do not know about e-Tilang, both the program and the flow of its implementation.